Interview of John E. Sater by Brian Shoemaker - Sater, John E. (Byrd Polar Research Center Archival Program, 2012)
The media can be accessed at the links below. Audio Part 1: http://streaming.osu.edu/knowledgebank/byrd/oral_history/John_Sater_1.mp3 Audio Part 2: http://streaming.osu.edu/knowledgebank/byrd/oral_history/John_Sater_2.mp3 Mr. Sater’s polar career began 1955 when he was in the Army as part of the First Engineering Arctic Task Force. This group studied methods of constructing snow compacted runways on the Greenland Ice Cap. Later he got a bachelors degree at Ohio State University under the tutelage of Dr Richard Goldthwaite. During the IGY he did surface motion studies on the McCall Glacier under a project funded by the Arctic Institute of North America. His career from this point on was centered about AINA and Arctic research although he had one tour in the Antarctic with the British. The interview was disjointed as he jumped around somewhat. There was some very revealing information, however. The following is pertinent: 1. While in the Army he was sent to Greenland (1955-56) as part of the First Engineer Arctic Task force that studied the construction of snow compacted runways on the central icecap. 2. Pointed out that the USAF was able to land C-124 Globemaster aircraft on the man-made runways and unload large Army tanks. Sater feels that the same type runways would be useful in Antarctica. Basically they used a heating device to melt the surface layer of snow and then sheep’s-foot construction roller to compact it. 3. During IGY he was part of the team that did motion studies on the McCall Glacier in the Romanzov Mountains, Alaska. Other team members included Dick Hubley (Station Leader), Bob Mason and Charles Keeler. Hubley committed suicide – he explains the details. 4. In 1960 Mr. Sater sailed to Antarctica on the Kista Dan as the U.S. Representative with the British Antarctic Survey. Sir Vivian Fuchs was in charge. The ship was frozen in “the ice” for a long period of time until the USS Glacier was able to free it. Scientific objectives were not met. 5. After IGY he returned to AINA where he helped ...